2019
DOI: 10.1017/s0376892919000079
|View full text |Cite
|
Sign up to set email alerts
|

Equity for Women and Marginalized Groups in Patriarchal Societies during Forest Landscape Restoration: The Controlling Influence of Tradition and Culture

Abstract: SummaryWe explore the difficulty of achieving equity for women in two forest and livelihood restoration (FLR) pilot projects, one each in Papua New Guinea (PNG) and the Philippines. We use institutional bricolage as a framework to explain the context and background of stakeholders’ decision-making and the consequent impact on equity and benefit distribution. In the Philippines, material and institutional support was initially successful in assisting participants to establish small-scale tree plantations. A str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A gender analysis of grassland management in Mongolia showed that although there is awareness of the need to increase gender equity, women are rarely fully included in decisions and leadership around community land management in herding communities, and this is then reflected in conservation and natural resource management projects (Ykhanbai et al, 2006). Therefore, simply having women present in decision-making fora without considering the societal context will not resolve this disparity (Staples & Natcher, 2015; Baynes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A gender analysis of grassland management in Mongolia showed that although there is awareness of the need to increase gender equity, women are rarely fully included in decisions and leadership around community land management in herding communities, and this is then reflected in conservation and natural resource management projects (Ykhanbai et al, 2006). Therefore, simply having women present in decision-making fora without considering the societal context will not resolve this disparity (Staples & Natcher, 2015; Baynes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of explicitly aligning PES project process with existing institutions is that, while this may be good for existing land holders and project outcomes, it may limit the transformative potential of PES: building PES on existing structures can simply reinforce existing power imbalances and structural inequalities that may be the root cause of many local social and environmental problems (Baynes et al, 2019;Esteve Corbera et al, 2020;Mahanty et al, 2013;vonHedemann, 2020). Thus, programmes will need to be critical about which existing institutions to engage with and how they do so.…”
Section: Discussionmentioning
confidence: 99%
“…Religious and cultural institutions must actively participate in educating society on the value of sustainable earth and environment. It has been observed that culture, tradition, and religion all overwhelmingly influence the psyche, politics, emotional intelligence, and approach to life of individuals; , hence, addressing a global issue such as plastic pollution requires a rethink of our educational systems and the roles they play in promoting a sustainable environment. Human behaviors are ranked as some of the main challenges to addressing environmental issues; however, educational, religious, cultural, and traditional organizations can influence the attitudes and behaviors of their members in terms of environmental issues and are best placed to convince the population of the dire need to manage and control plastic pollution through behavioral change and ethical best practice. , …”
Section: Opportunitiesmentioning
confidence: 99%